Symptoms and growth components of feijoa (Acca sellowiana [O. Berg] Burret) plants in response to the missing elements N, P, and K - Buitrago, Sebastián; Leandro, Manuel; Fischer, Gerhard (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
Plants often express deficiencies with visible abnormalities; however, it is necessary to obtain reliable information to make the proper diagnosis about the missing nutrients. Until now, research with this approach has not been carried out for crops such as feijoa (or pineapple guava). For this reason, the present investigation identified and described the symptoms produced in young feijoa plants due to poor fertilization of N, P, and K and its effect on some components of plant growth and development. To achieve this, different treatments were established: complete fertilization (control); complete fertilization -N; complete fertilization -P; complete fertilization -K; and one treatment with no element (negative control, H2O). We determined the symptoms associated with each deficiency by means of a photographic record and the description of the symptoms. Among these nutrients, N deficiency yielded the highest plant detriment, due to lower growth and a global pale green coloration, while -P plants showed foliar malformations and necrosis, -K plants exhibited the brown margin in old leaves, then turning necrotic, while young leaves showed a lack of turgor. Also, lack of N seriously affected apical growth, number of basal and apical shoots, and chlorophyll foliar content, while the -P and -K developed lower growth rate in the shoot than in the control. Such symptoms were registered after two months of treatment. This study indicated that the greatest affectation of the feijoa was due to a lack of nitrogen; and also P and K deficiencies showed symptoms and growth characteristics that were altered in the development of the plants.